Cancer preventive effect of a specific probiotic fermented milk components and cell walls extracted from a biomass containing L. acidophilus CL1285, L. casei LBC80R, and L. rhamnosus CLR2 on male F344 rats treated with 1, 2-dimethylhydrazine. (October 2016) - Desrouillères, Kerlynn; Millette, Mathieu; Jamshidian, Majid; Maherani, Behnoush; Fortin, Olivier; Lacroix, Monique
Highlights: Cell wall of three Lactobacillus strains demonstrated chemopreventive activity. Probiotic and its components reduced ACF count in DMH-treated rats. Fermented milk (FM) pellet induced the activity of Quinone reductase. FM reduced the β-glucosidase activity and induced the GST activity. Probiotic bacteria and their metabolites could prevent colorectal carcinogenesis. Abstract: The colon carcinogenesis was induced in male F344 rats by N, N-dimethylhydrazine (DMH). In addition to the DMH, four groups of rats received respectively fermented milk (FM), fermented milk supernatant, fermented milk pellet (P) and cell wall constitutes through gavage. All rats supplemented with probiotic formula and its components had significantly (p ≤ 0.05) lowered the count of aberrant crypt and the number of aberrant crypt foci as compared to the positive control (PC) group. Rats administrated with P were significantly (p ≤ 0.05) able to induce the activity of quinone reductase compared to rats in PC group. Rats administered with FM showed a significant lower activity (p ≤ 0.05) of β-glucuronidase. Rats in FM group showed also a reduced activity of β-glucosidase and an induction of the activity of glutathione S-transferase. These results indicate that the probiotic bacteria and the metabolite release during the fermentation process could prevent colorectal carcinogenesis.